NUMERICAL INVESTIGATION OF THE TURBULENT FLOW PARAMETERS DISTRIBUTION IN A PARTLY PERFORATED HORIZONTAL WELLBORE - Abdulwahid, Mohammed Abdulwahhab; Dakhil, Sadoun Fahad; Injeti, Niranjan Kumar (European Scientific Journal, ESJ, 2013)
The overall pressure drop in a horizontal wellbore used in the recovery of oil and gas industry was classified into four separate effects due to wall friction, increase in momentum, perforation roughness and type of fluid mixing. A perforated section is followed by a plain section for many horizontal wells. The additional pressure drop due to combined effect of perforation roughness and the type of fluid mixing was analyzed through numerical CFD and the results were compared with the experimental results of other researchers. The computations were based on the finite volume method with the SIMPLE algorithm standard Îµâˆ’kmodel. The pipe was used geometrically similar to the real perforated wellbore with 60 ÌŠ phasing, 6 SPF (shoot per foot) and the pitch of the perforations 60 mm (the number of perforations in this paper are less than experimental pipe). The parameters that are being investigated are pressure drops of the pipe and so far simulations have been carried out for an inlet pipe Reynolds numbers ranging from 28,773 to 90,153 for the total flow rate ratio ranging from 0% to 100%. Numerical simulations were performed using CFX of ANSYS FLUENT 13, where the governing equations of mass and momentum were solved simultaneously, using the two equations of standard k-Îµ turbulence model. As the rate of flow through the perforations increases i.e. with the increase in flow rate ratio, the total pressure increases due to large acceleration pressure drop for higher flow rate through the perforations. The increases in perforations number increase the total pressure drop and vice versa. The numerical results agreed with the experimental work.